2012
DOI: 10.1159/000336914
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation and Proteinases in Tumor Progression

Abstract: Chronic inflammation is an important risk factor for the development of cancers. The link between chronic inflammation and the risk of developing cancer is now well established. At least 20% of all cancers arise in association with infection and chronic inflammation. Inflammation and cancer are linked both along intrinsic (driven by genetic events causing malignancy) and extrinsic (driven by inflammatory conditions predisposing to tumor) pathways. Proteinases are key contributors to the breakdown and reconstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 142 publications
0
26
0
Order By: Relevance
“…Although the pathogenic impact of chronic inflammation has been proposed in tumor initiation and progression, the exact mechanism of this connection is still not completely elucidated [9]. It has been proposed that persistent inflammation is an indispensable prerequisite for the development of CRC: chronic inflammation and the increased turnover of epithelial cells contribute to cellular damage and molecular changes that transform inflamed mucosa to low-grade dysplasia (LGD), high-grade dysplasia (HGD) and finally CRC.…”
Section: The Role Of Inflammationmentioning
confidence: 99%
“…Although the pathogenic impact of chronic inflammation has been proposed in tumor initiation and progression, the exact mechanism of this connection is still not completely elucidated [9]. It has been proposed that persistent inflammation is an indispensable prerequisite for the development of CRC: chronic inflammation and the increased turnover of epithelial cells contribute to cellular damage and molecular changes that transform inflamed mucosa to low-grade dysplasia (LGD), high-grade dysplasia (HGD) and finally CRC.…”
Section: The Role Of Inflammationmentioning
confidence: 99%
“…It has been shown that cancer metastasis is a complex series of sequential processes: the initial transforming event; proliferation of transformed cells; the ability of tumor cells to avoid destruction by immune-response; nutrition supply to the tumor mass; local invasion and destruction of extracellular matrix components (ECM); migration of tumor cells; penetration of tumor cells through the blood vessel wall; embolization of tumor cells and adhesion to distant organs; arrest of cancer cells in the lumen of small blood vessels and lymphatics; reverse penetration of blood vessels and formation of distant metastases [510]. …”
Section: Events During Tumor Invasion and Metastasismentioning
confidence: 99%
“…Chemotactic factors can influence the direction of migration. Invasion of ECM is accomplished by cyclic reverberation of these three steps [7,1015]. …”
Section: Events During Tumor Invasion and Metastasismentioning
confidence: 99%
“…There is evidence supporting the hypothesis that inflammation participates in providing conditions that lead to cancer [26,27], and there are well known associations between inflammatory processes and cancer, such as inflammatory bowel disease and colorectal cancer [28,29], viral hepatitis B and C or alcoholic liver cirrhosis and hepatocarcinoma [30], chronic reflux esophagitis resulting in Barrett's esophagus and esophageal carcinoma [29], cervical infection by human papillomavirus and cervical cancer, prostatitis and prostate cancer, pancreatitis and pancreatic cancer, or gastric infection from Helicobacter pylori and gastric cancer [31,32].…”
Section: Mmps and Timps In Disease And Cancermentioning
confidence: 79%